(untitled) (Hoboken, N.J., 2007)
Combating the Threat of Pandemic Influenza: Drug Discovery Approaches consolidates the latest information on diverse approaches into one comprehensive resource. It is an invaluable, hands-on reference for researchers in medicinal chemistry, pharmaceutical chemistry, drug discovery, biochemistry, virology, microbiology, and public health.
Keywords: Antiviral agents,Influenza,Influenza, human,Antiviral agents,Drug Design; Chemotherapy,Drug therapy,Therapeutic use